2014
DOI: 10.1093/gerona/glu092
|View full text |Cite
|
Sign up to set email alerts
|

The Alcohol Paradox: Light-to-Moderate Alcohol Consumption, Cognitive Function, and Brain Volume

Abstract: Background. Studies of older persons show consumption of light-to-moderate amounts of alcohol is positively associated with cognitive function and, separately, is negatively associated with total brain volume (TBV). This is paradoxical as generally, cognitive function is positively associated with TBV. We examined the relationships of TBV, global cognitive function (GCF), and alcohol consumption in a population-based cohort of 3,363 men and women (b. 1907-1935) participating in the Age Gene/Environment Susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 39 publications
3
39
0
Order By: Relevance
“…The bivariate correlations between age, years of education, physical activity, and alcohol, known confounding variables of cognitive performance, 16 , 17 , 28 and the cognitive tests scores were examined. The Pearson’s r correlation was statistically significant and negative between age and the different cognitive tests scores ( r =−0.435, P <0.01).…”
Section: Resultsmentioning
confidence: 99%
“…The bivariate correlations between age, years of education, physical activity, and alcohol, known confounding variables of cognitive performance, 16 , 17 , 28 and the cognitive tests scores were examined. The Pearson’s r correlation was statistically significant and negative between age and the different cognitive tests scores ( r =−0.435, P <0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Alcohol consumption was categorized into 4 groups based on drinking status and current weekly alcohol consumption (drinks/week): abstainers, former drinkers, light to moderate (women 1–7; men 1–14) and heavy (women >7; men>14). 17 BMI was calculated as weight (kg) divided by height squared (m 2 ) and further categorized into 4 groups according to the WHO guidelines: underweight <18.5, normal weight 18.5–24.9, overweight 25–29.9 and obese >30. Fasting total cholesterol, HDL-cholesterol and triglyceride levels were determined on a Hitachi 912 instrument using comparable enzymatic procedures (Roche Diagnostics, Mannheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…For example, intracranial area and several regional brain volumes appear correlated with tests of premorbid and fluid intelligence and tests of visuospatial memory. Several studies that have examined these associations have shown conflicting results [145][146][147][148]. The collective findings of these studies, however, suggest that light to moderate alcohol consumption, particularly wine, is associated with both improved cognition and larger total brain volume, which may be reduced in individuals consuming heavier amounts of alcohol.…”
Section: Regional Brain Volumesmentioning
confidence: 99%